Oedipus’ Freudian slips: language, kinship and tyranny - Kucharski, Janek (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
This paper deals with the linguistic aspect of tragic irony in the Oedipus Rex. It begins with the observation that several ambiguous expressions in the play telegraph their double meaning through various kinds of linguistic slips. It is argued that these slips occur on three distinct levels: semantics, syntax and pragmatics. There follows an analysis of several examples under each of these three headings. The paper concludes with the observation that when it comes to the question of Oedipus’ familial relationships and the legitimacy of his rule in Thebes, language itself fails the hero and defies his attempts at controlling it.